A stretchable, high-voltage and biobased microsupercapacitor using laser induced graphene/MnOx electrodes on cotton cloth. (July 2022) - Lu, Longsheng; Zhang, Duankang; Xie, Yingxi; Wang, Wentao
Abstract: The rapid development of wearable electronics has put forward a great demand for flexible microsupercapacitors (MSCs) that can work normally under extreme deformation, but its green, efficient and pollution-free manufacturing is still a daunting challenge. Here, natural cotton cloth is pre‑carbonized as the precursor and coated with gelatin-mediated manganese (Mn) ion ink for CO2 laser scribing. A biobased laser-induced graphene/manganese oxide (LIG/MnO x ) MSC is assembled on a cardboard substrate, showing an areal capacitance of 54.97 mF/cm 2 at a current density of 0.05 mA/ cm 2 and an areal energy density of 7.63 μWh cm −2 at a power density of 78.93 μW cm −2 . These excellent electrochemical performances are attributed to the core-shell structure of LIG/MnO x which provides balanced pseudocapacitance and double-layer capacitance behaviors as well as the stable mechanical properties. Using a simple series-parallel electrode design combined with the kirigami cutting craftwork, a highly stretchable MSC with rated voltage of 60 V is assembled, which can simultaneously light up 20 LEDs for more than 30s during 0– 200% dynamic stretching process, providing a promising power platform for wearable electronics. Graphical abstract: Unlabelled Image Highlights: A biobased LIG/MnO x MSC is fabricated using natural cotton cloth, gelatin-mediated ink and cardboard. The LIG/MnO x MSC can deliver an areal energy density of 7.63 μWh cm −2 at a power density of 78.93 μW cm −2 . By series-parallel and Kirigami cutting design, a stretchable MSC with rated voltage of 60 V is prepared.